(untitled) (Research, Society and Development, 2023)
Gastritis is an inflammation of the intestinal mucosa, which can be acute, which appears suddenly, or chronic, which takes time to be treated and evolves slowly. The symptoms of gastritis are usually pain, heartburn and a strong burning sensation. Regarding treatment, many studies have evaluated the effects of espinheira santa as a way to treat gastritis, since this medicine has antibacterial properties and helps control bile secretions, improving the absorption of fats in the intestines. Therefore, the general objective of this work is to analyze the effectiveness of the herbal medicine of espinheira santa for the treatment of the gastrointestinal disease gastritis. As for the methodology, this work is a descriptive and exploratory study based on a literature review and on conducting research and collecting scientific data organized through the investigation of articles associated with the object of study and published between 2015 and 2022. In the results, the general aspects of the gastrointestinal disease gastritis were analyzed; described the effects of the herbal medicine espinheira santa specifically for the treatment of gastritis, based on its effectiveness for said treatment; recognized that espinheira santa has substances that improve the symptoms of gastritis, but that the use of this herbal medicine should not replace the medicine prescribed by the doctor, because, although it helps, it does not constitute a definitive treatment for this disease.